Chemotherapy and Cardiotoxicity: advances and challenges in cardio-oncology – An integrative review (Research, Society and Development, 2025)
Introduction: The exponential increase in cancer cases has had a widespread impact, culminating in the advancement of drugs and chemotherapies involved in treatment. Among the most commonly used pharmacological classes are anthracyclines and anti-HER2 agents, with doxorubicin and trastuzumab being the main examples, respectively. These drugs are frequently described with a causal association with chemotherapy-induced cardiotoxicity. Cardiotoxicity is defined as the confirmed presence of a new cardiovascular alteration during or after treatment without other possible etiological causes to justify the condition. This represents a significant complication during cancer treatment, highlighting the importance of the cardio-oncologist’s involvement in the early identification of cardiovascular involvement, its monitoring, and treatment. Objective: To establish an updated review on the topic of cardiotoxicity related to chemotherapeutic agents, trastuzumab and doxorubicin, and the importance of developing prevention and treatment strategies. Methodology: A non-experimental, descriptive research will be conducted, through an integrative literature review of articles found on the official websites of PubMed® and SciELO®, available between the years 2018 and 2024, and publicly accessible. Conclusion: It is concluded that there is no doubt regarding the relationship between chemotherapeutic agents and cardiotoxicity. The importance of regular cardiological follow-up through complementary exams is reinforced, aiming at early recognition and intervention to prevent irreversible cardiovascular damage.